Simulation and experiment on transitional behaviours of multiphase flow in a hydrocyclone. (20th August 2015) - Wang, Chenxiang; Ji, Chen; Zou, Jun
<x xml:space="preserve">Abstract</x> This paper presents an investigation of transitional behaviours of multiphase flow in a hydrocyclone. The experiment and simulation results reveal the existence of two stages of the transition period of gas‐liquid flow. The numerical model combined with the large eddy simulation model (LES), the volume of fluid model (VOF), and the Lagrangian discrete phase model (DPM) approach is used to simulate the multiphase flow in a hydrocyclone. The applicability of this approach with a 2‐step simulation strategy has been verified by the close agreement between the calculated and measured flow fields. Particle motion upon entering the hydrocyclone indicates the separation mechanism of a hydrocyclone. Moreover, a parameter of the hydrocyclone, separation cycle time Tc, is proposed to describe the dynamic characteristics of the particle residence time.